Labeling, responsible and sustainable food consumption: Consumer perception in Costa Rica - Gómez Castillo, David; Barrantes Aguilar, Luz; Quesada Quesada, Yuliana (Agronomía Mesoamericana, 2025)
Introduction. Over the last few decades, there has been growing interest on the part of consumers in sustainable agri-food products. As a result, voluntary standards have emerged as a tool to promote sustainability in production and consumption in agri-food value chains. Objective. To evaluate the profile of consumers and the degree of knowledge of sustainability seals for agricultural products in Costa Rican markets. Materials and methods. During October and November 2021, a nationwide virtual survey was conducted through the Qualtrics platform, from which 397 valid responses were collected. The sustainability seals considered were certifications of organic production, fair trade, denomination of origin, nation brand Essential Costa Rica, and carbon neutral. The Poisson regression model (PRM) was used to study the behavior of the variables, using Stata software version 16.0. Results. The Essential Costa Rica seal is the most recognized. People residing in the Greater Metropolitan Area (GAM) are more familiar with various seals. The income variable turned out to be a significant factor; those with higher incomes tend to identify and value sustainability seals more. The levels of knowledge and consumption of certified products increase when the consumer has some link to the agricultural sector. Conclusions. People’s interest in certified products is not reflected in their purchasing behavior, due in part to the price of the products, lack of trust or excessive information on labels. The findings of the study allow companies to define their marketing strategies according to the characteristics of the consumers of these differentiated products.